Linking up: The role of institutions and farmers in forage seed exchange networks of Southeast Asia - Leyte, James Elwyn D.; Delaquis, Erik; Van Dung, Pham; Douxchamps, Sabine (Springer, 2022)
In Southeast Asia, access to improved forages remains a challenge for smallholder farmers and limits livestock production. We compared seed exchange networks supporting two contrasting livestock production systems to identify bottlenecks in seed availability and determine the influences of the market, institutions, and cultural context of seed exchange, using interview-based methods for ‘seed tracing’ and network analysis. Government agencies were the primary sources of high-quality genetic materials, with secondary diffusion in the Philippines dairy case being dominated by key individuals in active cooperatives. In the Vietnamese beef-oriented production context, farmer to farmer dissemination was more substantial. In both cases, formal actors dominated where botanical seed was exchanged, while farmers frequently exchanged vegetatively propagated materials among themselves. To improve access to forage seed in these contexts, government agencies and development actors should coordinate quality seed production upstream while supporting the creation of appropriate training, structures, and incentives for seed exchange network improvement downstream.